The Role of Technological Pedagogical Content Knowledge (TPACK) on Motivation of Arabic Learning: Case study at Dar Ath-Thalibat Arabic Learning Center - Nurul Hidayah; Hafidah; Muhammad Nanang Qosim; Cahyani Windarto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In a world where communication is becoming more and more integrated, learning Arabic is crucial for enhancing both language and cultural competency. The Technology-Pedagogical Content Knowledge (TPACK) approach seems to be a useful strategy for increasing student engagement. This study looks into how TPACK competency affects the Arabic language learning process. This study used a descriptive methodology and a qualitative strategy to gather data through literature review techniques and observational investigations of relevant research on the subject at hand. The study's findings indicate a special connection between TPACK competency and student motivation. The material is then presented in video format for speaking using the web-based learning platform. The varied findings analysed in this study indicate that the Teacher TPACK competency can help teachers develop more engaging lessons while also enhancing student motivation and engagement.